2006
DOI: 10.1111/j.1365-2567.2005.02312.x
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal macrophages suppress T‐cell activation by amino acid catabolism

Abstract: SummaryT-lymphocyte activation triggered by anti-CD3, endogenous or exogenous superantigen, and mitogens was suppressed in a cell-dose-dependent fashion by peritoneal cavity (PerC) leucocytes. Study of lymphocyte-deficient mice and the use of multiparameter fluorescence-activated cell sorter analyses revealed that macrophages were responsible for this form of immune regulation. Interferon-c was essential to trigger suppression, which, by enzyme inhibition studies, was shown to be the result of tryptophan and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 56 publications
(170 reference statements)
0
60
1
Order By: Relevance
“…Kupffer cells (KCs), resident liver macrophages, are long lived and abundant, representing 15 to 20% of the total liver cell population (42,68). Resting KCs, one of the first types of immune cells to be exposed to materials absorbed in the gut, contribute to the generally tolerogenic environment in the liver (3,41,68,77,86), including suppression of T-cell activation (51). Nevertheless, during immune responses, KCs, like circulating monocytes drawn into the liver, can be activated by various stimuli (17,19,22,26,34,47,57,59,64,73,77,83) (Table 1).…”
Section: Macrophages In the Livermentioning
confidence: 99%
“…Kupffer cells (KCs), resident liver macrophages, are long lived and abundant, representing 15 to 20% of the total liver cell population (42,68). Resting KCs, one of the first types of immune cells to be exposed to materials absorbed in the gut, contribute to the generally tolerogenic environment in the liver (3,41,68,77,86), including suppression of T-cell activation (51). Nevertheless, during immune responses, KCs, like circulating monocytes drawn into the liver, can be activated by various stimuli (17,19,22,26,34,47,57,59,64,73,77,83) (Table 1).…”
Section: Macrophages In the Livermentioning
confidence: 99%
“…57, 2008 Regulatory T cells and macrophages 567 and resulted in degradation of tryptophan. Seven years later, Matlack and his colleagues [35] confirmed and extended this mechanism in mice. They found that through tryptophan and arginine catabolism, peritoneal macrophages inhibited T lymphocyte activation in a cell dose-dependent and MHCindependent fashion.…”
Section: Suppression Of Effector T Cells By Subsets Of Macrophagesmentioning
confidence: 64%
“…As a type of APCs, but different from DCs, macrophages may mainly mediate anergy in allogeneic T cells in humans and mice, supporting the concept that resting macrophages maintain peripheral immune tolerance in vivo [19,35]. Several studies show that macrophages are tolerogenic in tumors and inflammatory diseases [36,37].…”
Section: Suppression Of Effector T Cells By Subsets Of Macrophagesmentioning
confidence: 98%
“…In particular, T cells are exposed to this microenvironment as they are recruited to participate in the immune response. T cell proliferation is known to be susceptible to the effects of enzymes expressed by APCs that catabolize and lower concentrations of amino acids, such as tryptophan and arginine, in mixed leukocyte reactions (19,56). With respect to IDO1, this is in part due to an amino acid stress response since proliferation can be restored through the addition of excess tryptophan (5,19).…”
Section: Discussionmentioning
confidence: 99%